Protocols for Pre-Field Screening of Mutants for Salt Tolerance in Rice, Wheat and Barley - Bado, Souleymane; Forster, Brian P.; Ghanim, Abdelbagi; Jankowicz-Cieslak, Joanna; Günter, Berthold; Luxiang, Liu (Springer International Publishing : Imprint: Springer, 2016)
This book offers effective, low-cost and user-friendly protocols for the pre-field selection of salt-tolerant mutants in cereal crops. It presents simple methods for measuring soil salinity, including soil sampling and the analysis of water-soluble salts, and describes a detailed, but simple, screening test for salt tolerance in rice, wheat and barley seedlings, which uses hydroponics. The protocols are devised for use by plant breeders and can be easily accommodated into breeding practice. .